Mutual Interaction between Human Multipotent Adult Progenitor Cells and NK Cells. Issue 9 (September 2014) - Jacobs, Sandra A.; Plessers, Jeroen; Pinxteren, Jef; Roobrouck, Valerie D.; Verfaillie, Catherine M.; Van Gool, Stefaan W.
Human multipotent adult progenitor cells (hMAPCs) are isolated from bone marrow with a more extensive expansion capacity compared to human mesenchymal stem cells (hMSCs) and with the ability to differentiate into endothelium. Like hMSCs, hMAPCs inhibit T-cell proliferation induced by alloantigens. In this study, we tested the interaction between hMAPCs and natural killer (NK) cells. We assessed the susceptibility of hMAPCs to NK cell-mediated lysis and the immunomodulation of hMAPCs on NK cell function during IL-2-driven stimulation and the cytolytic effector phase. Human MAPCs express the ligands PVR and ULBP-2/5/6, which are recognized by activating NK cell receptors. However, they also express MHC class I molecules, which induce inhibitory signals in NK cells. Freshly isolated NK cells at different effector:target ratios did not kill hMAPCs as assessed by an MTT and 51 Cr-release assay, while hMAPCs impaired the cytotoxic activity of resting NK cells against the NK-sensitive K562 leukemia cell line. By contrast, IL-2-stimulated NK cells were capable of killing hMAPCs, and preactivated NK cells were not influenced during their cytotoxic effector function against K562 cells by hMAPCs. When added during the 6-day preactivation phase with IL-2, hMAPCs dose-dependently reduced NK cell proliferation in an IDO-dependent manner, but they did not influence the induction of cytotoxic capacity by IL-2. This study indicates that human MAPCs mutually interact with NK cells.